A concentration-independent micro/nanofluidic active diode using an asymmetric ion concentration polarization layer. Issue 33 (15th June 2017) - Lee, Hyekyung; Kim, Junsuk; Kim, Hyeonsoo; Kim, Ho-Young; Lee, Hyomin; Kim, Sung Jae
Abstract : The new class of micro/nanofluidic diodes with an ideal perm-selective membrane were demonstrated at a wide concentration range from 10 −5 M to 3 M. Moreover, the rectification factor was actively controlled by adjusting the external convective flows. Abstract : Over the past decade, nanofluidic diodes that rectify ionic currents ( i.e. greater current in one direction than in the opposite direction) have drawn significant attention in biomolecular sensing, switching and energy harvesting devices. To obtain current rectification, conventional nanofluidic diodes have utilized complex nanoscale asymmetry such as nanochannel geometry, surface charge density, and reservoir concentration. Avoiding the use of sophisticated nano-asymmetry, micro/nanofluidic diodes using microscale asymmetry have been recently introduced; however, their diodic performance is still impeded by (i) low (even absent) rectification effects at physiological concentrations over 100 mM and strong dependency on the bulk concentration, and (ii) the fact that they possess only passive predefined rectification factors. Here, we demonstrated a new class of micro/nanofluidic diode with an ideal perm-selective nanoporous membrane based on ion concentration polarization (ICP) phenomenon. Thin side-microchannels installed near a nanojunction served as mitigators of the amplified electrokinetic flows generated by ICP and induced convective salt transfer to the nanoporous membrane, leading to actively controlled micro-scale asymmetry. Using this device, current rectifications were successfully demonstrated in a wide range of electrolytic concentrations (10 −5 M to 3 M) as a function of the fluidic resistance of the side-microchannels. Noteworthily, it was confirmed that the rectification factors were independent from the bulk concentration due to the ideal perm-selectivity. Moreover, the rectification of the presenting diode was actively controlled by adjusting the external convective flows, while that of the previous diode was passively determined by invariant nanoscale asymmetry.